A New Enigmatic, Tubular Organism from the Ediacara Member, Rawnsley Quartzite, South Australia. (March 2014) - Joel, Lucas V.; Droser, Mary L.; Gehling, James G.
Abstract : Here we reconstruct a new tubular, serially divided organism with a bilateral morphology from the Ediacaran of South Australia. The organism, Plexus ricei new genus new species, was a broadly curving tube that resided on the Ediacaran seafloor. Plexus ricei individuals range in size from 5 to 80 cm long and 5 to 20 mm wide, and are comprised of two main components: a rigid median tubular structure and a fragile outer tubular wall. Plexus ricei is preserved as an external mold on bed soles, and as a counterpart cast on bed tops in sandstones interpreted to represent deposition between storm and fairweather wave-base. The phylogenetic affinities of P. ricei are uncertain; P. ricei symmetry implies a bilaterian origin, but a lack of defined anterior and posterior ends precludes definitive assignment.